Age‐ and sex‐related reference intervals of lymphocyte subsets in healthy ethnic Han Chinese children. (7th July 2015) - Jia, Liting; Li, Jing; Zhang, Yuchao; Shi, Ying; Yuan, Enwu; Liu, Junjie; Wang, Peng; Rong, Shouhua; Xing, Jinfang; Tian, Yuan; Li, Junfang
Abstract: Immunophenotyping of blood lymphocytes has become an important tool in the diagnosis of immunologic and hematologic disorders such as immunodeficiencies, lymphoproliferative and autoimmune diseases. Lymphocyte subsets include total T‐cells (CD3 + ), TH (T helper, CD3 + CD4 + ), TC (cytotoxic T cells, CD3 + CD8 + ), B‐cells (CD3 − CD19 + ), and NK‐cells (CD3 − CD16 + CD56 + ). Specific lymphocyte subset reference intervals should be locally established for meaningful comparison and to obtain an accurate interpretation of the results. Reference intervals of lymphocyte subsets for Chinese children are scarce. We performed dual‐platform flow cytometry to determine the reference intervals of the percentages and absolute counts of lymphocyte subsets, including total T‐cells, TH cells, TC cells, B‐cells, and NK‐cells in 1, 027 ethnic Han children aged 4 months to 7 years in Henan, China. The children were divided into seven age groups. The percentages and absolute counts differed significantly with age, with the percentages of TH cells and B cells and the CD4/CD8 ratio peaking during the first year, while the percentages of total T cells, TC cells, and NK cells were obviously increased with age; girls showed a trend toward having a higher percentage of TH cells and a higher CD4/CD8 ratio than boys. The absolute counts of lymphocyte subsets peaked during first year and then decreased steadily with age. The reference intervals of lymphocyte subsets among children from China differed from the reported values in Hong Kong, the United States, Cameroon, and Italy. The differences observed could be due to genetic and environmental factors, coupled with the methodology used. The reference intervals of lymphocyte subsets could be used as initial national reference ranges in guidelines for children aged 4 months to 7 years. © 2015 International Society for Advancement of Cytometry